Students' academic self-perception - Arnaud Chevalier; Steve Gibbons; Andy Thorpe; Martin Snell; Sherria Hoskins (Institute for the Study of Labor (IZA), 2007)
Participation rates in higher education differ persistently between some groups in society. Using two British datasets we investigate whether this gap is rooted in students' misperception of their own and other's ability, thereby increasing the expected costs to studying. Among high school pupils, we find that pupils with a more positive view of their academic abilities are more likely to expect to continue to higher education even after controlling for observable measures of ability and students' characteristics. University students are also poor at estimating their own test-performance and over-estimate their predicted test score. However, females, white and working class students have less inflated view of themselves. Self-perception has limited impact on the expected probability of success and expected returns amongst these university students.
Keywords: 370; Test performance; self-assessment; higher education participation; academic self-perception; Bildungsinvestition; Studienfinanzierung; Schüler; Studierende; Meinung; Großbritannien